Does rising import competition harm local firm productivity in less advanced economies? Evidence from the Vietnam's manufacturing sector. Issue 1 (2nd January 2016) - Doan, Tinh; Nguyen, Son; Vu, Huong; Tran, Tuyen; Lim, Steven
Abstract : This paper examines whether rising import penetration has an effect on the productivity of domestic firms. The study uses data on a 10-year unbalanced panel of firms in the manufacturing sector in Vietnam from 2000 to 2009. Panel and instrumental variable methods are used to control firm heterogeneity and endogeneity of import penetration. We find statistically significant and negative effects of import competition on local firms' productivity, but the effect in terms of magnitude is economically small. Further investigation shows no clear evidence of variations in the effects by firm size and technological level. However, we find that rising import penetration is associated with the likelihood of firm death.